Revealing Our Superpowers: An Autoethnography on Childhood Abuse and How It Shapes Educators - Lori Goodson (Educational Considerations, 2019)
This article uses auto ethnography as research as the author examines her own childhood abuse and how it has shaped her as an educator who has taught at the middle level, high school, and university. Through her experiences, she has determined that teachers' personal stories significantly affect their development as educators. Through their teaching, their own stories--and the trauma and issues they have overcome--become their superpowers in aiding their students' perseverance.
Keywords: childhood abuse; teachers; auto ethnography; PTSD; teacher stories